The Role of Entrepreneurial Competencies as a mediator in the relationship between Microfinance and Small Business Growth - Mohd Rosli Mohamad; Syamsuriana Sidek (2013)
This paper aims to advance the knowledge about the relationship between microfinance, entrepreneurial competencies, and small business growth. In contrast to previous works in the field of small businesses, this paper aims to provide empirical evidence that entrepreneurial competencies mediate the relationship between microfinance and small business growth. The paper formulates three hypotheses from previous literature review. These hypotheses are tested using the Structural Equation Modeling with data collected from 243 microfinance participants. The findings indicate that microfinance has a strong association with small business growth. However, the results provide evidence that entrepreneurial competencies play a partial mediating role between microfinance and small business growth. The small sample size, which was dominated by small businesses, was the major limitation of the study. The sample size and distribution also inhibited the comparison of the results between industry sectors. This result can be used in the study on the impact of microfinance toward small business growth in the future. By testing the interaction effect of microfinance and entrepreneurial competencies in small business growth, this paper advances previous works on this area, by looking at the relationship between microfinance and entrepreneurial competencies on small business growth simultaneously.